2023
DOI: 10.1021/acs.jafc.3c01606
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Alters Lipid Metabolism Processes via H3K9ac Epigenetic Modification in Dairy Goat

Jiao Wu,
Jun Luo,
Qiuya He
et al.

Abstract: Goat milk is increasingly recognized by consumers due to its high nutritional value, richness in short-and mediumchain fatty acids, and richness in polyunsaturated fatty acids (PUFA). Exogenous supplementation of docosahexaenoic acid (DHA) is an important approach to increasing the content of PUFA in goat milk. Several studies have reported benefits of dietary DHA in terms of human health, including potential against chronic diseases and tumors. However, the mechanisms whereby an increased supply of DHA regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…NAT10 is a regulator of ac4C modification, exerting functions in various tumors by modifying the acetylation of tRNA, rRNA, and mRNA [17] , [18] , [19] , [20] , [21] , [22] , [23] . According to data analysis and bioinformatics prediction, we determined that NAT10 could target FASN, which is a lipid metabolism-related gene [ 55 , 56 ]. Through further investigation, we identified that NAT10 could stabilize FASN expression to induce macrophage M2 polarization by mediating the ac4C modification of FASN.…”
Section: Discussionmentioning
confidence: 99%
“…NAT10 is a regulator of ac4C modification, exerting functions in various tumors by modifying the acetylation of tRNA, rRNA, and mRNA [17] , [18] , [19] , [20] , [21] , [22] , [23] . According to data analysis and bioinformatics prediction, we determined that NAT10 could target FASN, which is a lipid metabolism-related gene [ 55 , 56 ]. Through further investigation, we identified that NAT10 could stabilize FASN expression to induce macrophage M2 polarization by mediating the ac4C modification of FASN.…”
Section: Discussionmentioning
confidence: 99%